Designing User Interface/User Experience of Layanan Informasi Kampus (LIK) Using Lean User Experience (Lean UX) Method at Dr. Soetomo University - Saputra, Erwin; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
LIK is a web-based academic information system application at Dr. Soetomo with the aim to provide students with academic information. Based on a review of the LIK application similarweb website, there are few visitors due to the user interface / user experience that is less attractive and less responsive to the mobile web display, whereas the number of users accessing the mobile web reaches 93%. In addition, from the results of the questionnaire to 30 users, it is known that the current ease of application when accessed via a smartphone is only 30% who agree. The solution is to design a user interface / user experience specifically for mobile devices using the Lean UX method, consisting of 4 stages: Declare Asumptions, Create an MVP, Run an Experiment, Feedback and Research. The test was conducted to 30 students at Dr. Soetomo with 2 iterations. From the first iteration, the prototype success rate reached 83%, while the second iteration reached 87% which indicated an increase in UI / UX than before. This shows that the resulting prototype is quite good in terms of user interface / user experience so that the prototype can be easily used for the first time on a mobile display.